2010
DOI: 10.1371/journal.pone.0014271
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of AAT•ATT Triplet Repeats in Escherichia coli Is Silenced by H-NS and IS1E Transposition

Abstract: BackgroundThe trinucleotide repeats AAT•ATT are simple DNA sequences that potentially form different types of non-B DNA secondary structures and cause genomic instabilities in vivo.Methodology and Principal FindingsThe molecular mechanism underlying the maintenance of a 24-triplet AAT•ATT repeat was examined in E.coli by cloning the repeats into the EcoRI site in plasmid pUC18 and into the attB site on the E.coli genome. Either the AAT or the ATT strand acted as lagging strand template in a replication fork. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Within the ES the 70 bp repeats appear to be a pronounced site of VSG RNA-DNA hybrid accumulation, given the strongest R-loop ES enrichment is seen in this location in Tbrh1 -/- mutants. R-loops may form more readily on the 70 bp repeats due to their sequence composition: individual 70 bp repeats show considerable size and sequence variation but are, in part, comprised of (TRR) repeats [15, 75] that can become non-H bonded [76] and promote recombination [77] when transcribed. Increased DRIP-seq signal across the active VSG ES of Tbrh1 -/- mutants might therefore be most readily explained by R-loops forming initially in the 70 bp repeats and extending back toward the RNA Pol I promoter due to retrograde spreading of the VSG ES transcription blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Within the ES the 70 bp repeats appear to be a pronounced site of VSG RNA-DNA hybrid accumulation, given the strongest R-loop ES enrichment is seen in this location in Tbrh1 -/- mutants. R-loops may form more readily on the 70 bp repeats due to their sequence composition: individual 70 bp repeats show considerable size and sequence variation but are, in part, comprised of (TRR) repeats [15, 75] that can become non-H bonded [76] and promote recombination [77] when transcribed. Increased DRIP-seq signal across the active VSG ES of Tbrh1 -/- mutants might therefore be most readily explained by R-loops forming initially in the 70 bp repeats and extending back toward the RNA Pol I promoter due to retrograde spreading of the VSG ES transcription blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Within the ES the 70 bp repeats appear to be a pronounced site of VSG RNA-DNA hybrid accumulation, given the strongest R-loop ES enrichment is seen in this location in Tbrh1 -/- mutants. R-loops may form more readily on the 70 bp repeats due to their sequence composition: individual 70 bp repeats show considerable size and sequence variation but are, in part, comprised of (TRR) repeats (15, 66) that can become non-H bonded (67) and promote recombination (68) when transcribed. Increased DRIP-seq signal in the active VSG ES of Tbrh1 -/- mutants is therefore most readily explained by R-loops forming initially in the 70 bp repeats and extending back toward the RNA Pol I promoter due to retrograde spreading of the VSG ES transcription blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly we have recently found that trinucleotide repeats AAT can also adopt curved DNA in E.coli, which can be repressed by H-NS and its stimulated IS1E transposition (Pan et al, 2010) …”
Section: Curved Dnamentioning
confidence: 99%